Analysis Implementation Of ‘Kurikulum Merdeka’ and ‘Project Penguatan Profil Pelajar Pancasila’ In High Schools (Case Study at Smk Ti Bali Global Denpasar) - Ni Putu Yuniarika Parwati; Lasmawan, Ni Wayan; Suharta, I Gusti Putu (International Journal of Applied Science and Sustainable Development (IJASSD), 2024)
This research was conducted because of the policy regarding the curriculum, namely the implementation of an Kurikulum Merdeka which focuses on students' abilities/character. So researchers are interested in studying the implementation of the Kurikulum Merdeka and the implementation of the Project for Strengthening the Pancasila Student Profile at SMK TI Bali Global Denpasar. This research uses a qualitative method with a descriptive approach. This research method aims to describe, interpret and understand phenomena or events that are occurring in the field. . The sources of informants in this research were school supervisors, principals, deputy principals and teachers. From the results of observations, interviews and documentation carried out at SMK TI Bali Global Denpasar, the Merdeka Curriculum has been implemented well even though there are several obstacles. However, schools and educators have tried to implement the Kurikulum Merdeka as well as possible in accordance with the goals to be achieved. In implementing the Project for Strengthening the Pancasila Student Profile at SMK TI Bali Global Denpasar, it was divided into three cycles. Each cycle students carry out projects with different themes. So that in one academic year, students take part in three projects which have been carried out well. Meanwhile, the obstacles to implementation are internal factors, namely learning planning and time management. External factor barriers are: student heterogeneity, infrastructure and the role of parents.